Hydrate phase equilibrium of ternary gas mixtures containing carbon dioxide, hydrogen and propane - Babu, Ponnivalavan; Yang, Ting; Veluswamy, Hari Prakash; Kumar, Rajnish; Linga, Praveen (Journal of Chemical Thermodynamics, 2013)
Hydrate phase equilibrium of the ternary guest mixtures containing carbon dioxide, hydrogen and propane at two different compositions were determined. Addition of mole composition of 2.5% propane to the fuel gas (CO2 (40%)/H-2 (60%)) mixture reduces the hydrate formation conditions by 66% at the temperature of 278.4 K. A Clausius-Clapeyron plot for the experimental results was plotted and from the slope, the enthalpy of hydrate dissociation was calculated. The enthalpy of dissociation of the mixed hydrate formed from a ternary gas mixture containing mole composition 38.1% CO2, 59.4% H-2 and 2.5% C3H8 was found to be 110 kJ.mol(-1) and hence it was concluded that the mixed hydrate formed structure II (sII) hydrates. Whereas for the ternary gas mixture containing mole composition 80.0% CO2, 18.8% H-2, and 1.2% C3H8, the enthalpy of dissociation of the mixed hydrate was found to be 78 kJ.mol(-1) and hence we believe the mixed hydrate formed structure I (sI) hydrate. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Phase equilibrium; Pre-combustion; Thermodynamics

Medium pressure hydrate based gas separation (HBGS) process for pre-combustion capture of carbon dioxide employing a novel fixed bed reactor - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (International Journal of Greenhouse Gas Control, 2013)
This work presents an effective medium pressure hydrate based gas separation (HBGS) process for pre-combustion carbon dioxide capture in a novel fixed bed column. 2.5 mol% propane was added to the fuel gas mixture as an additive to decrease the operating pressure of the HBGS process. Hydrate formation kinetics was investigated at three different pressures (4.5, 5.5 and 6.0 MPa respectively) and at 274.15 K. The performance of silica sand and silica gel as a medium was evaluated. In silica sand bed, multiple nucleation events were observed. In silica gel bed, the gas uptake and water conversion to hydrates was significantly low at any given driving force than that obtained in silica sand bed. Experiments at different water saturation levels (50, 75 and 100%) in silica sand bed were investigated at 6.0 MPa and 274.15 K. It was found that at 50% water saturation, gas consumed for hydrate formation and water conversion to hydrates was almost three times that at 100% saturation. Water to hydrate conversions of up to 64.3% was achieved after 4 h of hydrate formation for the 50% water saturated silica sand bed. Our study presents an opportunity to scale up the HBGS process for CO2 capture with enhanced kinetics by employing a fixed bed reactor configuration. Decomposition experiments at a driving force of Delta T of 10 K and 23K were carried out to recover the gas consumed for hydrate formation and it was found that Delta T of 23 K was sufficient to recover the hydrated gas. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Gas hydrates; Global warming; Pre-combustion; Separation

Pre-combustion capture of carbon dioxide in a fixed bed reactor using the clathrate hydrate process - Babu, Ponnivalavan; Kumar, Rajnish; Linga, Praveen (Energy, 2013)
Hydrate based gas separation (HBGS) process with silica sand and silica gel as contact medium was employed to capture CO2 from fuel gas mixture. Gas uptake measurement at three different pressures (7.5, 8.5 and 9.0 MPa) and 274.15 K were conducted for hydrate formation kinetics and overall conversion of water to hydrate, rate of hydrate formation were determined. Water conversion of up to 36% was achieved with silica sand bed compared to 13% conversion in the silica gel bed. Effect of driving force on the rate of hydrate formation and gas consumption was significant in silica sand bed whereas it was found to be insignificant in silica gel bed. Hydrate dissociation experiments by thermal stimulation (at constant pressure) alone and a combination of depressurization and thermal stimulation were carried out for complete recovery of the hydrated gas. A driving force of 23 K was found to be sufficient to recover all the hydrated gas within 1 h. This study indicates that silica sand can be an effective porous media for separation of CO2 from fuel gas when compared to silica gel. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrates; Gas separation; Global warming; Pre-combustion